Efektivitas Media Kartu Kata Bergambar dalam Meningkatkan Kemampuan Bahasa Ekspresif Anak Disabilitas Rungu - Oktaviani, Silvi; Safaruddin, Safaruddin; Efrina, Elsa; Nasri, Yosa Yulia (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Children with hearing disabilities experienced barriers in language development, particularly expressive language, which resulted in limitations in conveying ideas, desires, and feelings verbally. This condition required the use of visual and concrete learning media to support language development. This study aimed to determine the effectiveness of picture word card media in improving the expressive language skills of children with hearing disabilities at SLB N Sungai Penuh. The study used a Single Subject Research (SSR) approach with an A–B–A design consisting of an initial baseline condition (A1), an intervention phase (B), and a final baseline condition (A2). The research subject was a child with severe hearing impairment who experienced expressive language delay. Data were collected through direct observation by recording scores of the child’s ability to verbally name nouns and were analyzed using visual graphic analysis. The results showed that the subject’s expressive language ability in the A1 phase was at a low and stable level, increased during the intervention phase, and remained increased and stable in the A2 phase. These findings indicated that picture word card media were effective in improving the expressive language skills of children with hearing disabilities and could be used as an applicable alternative learning medium in special schools.